2002
DOI: 10.1007/s00125-002-0877-7
|View full text |Cite
|
Sign up to set email alerts
|

Hypoglycaemia unawareness and the brain

Abstract: The intention of this paper is to critically review the current state of knowledge of the role of the brain in the syndrome of hypoglycaemia unawareness.Both the role of the brain in the detection of hypoglycaemia and initiation of the counterregulatory responses and the function of the cerebral cortex during acute hypoglycaemia are considered. The evidence for and against the brain as the primary site of mammalian hypoglycaemia sensing and the mechanisms whereby such sensing may occur and change in hypoglycae… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
19
0

Year Published

2002
2002
2020
2020

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(19 citation statements)
references
References 95 publications
(40 reference statements)
0
19
0
Order By: Relevance
“…In line with this concept cerebral glucose concentrations measured by magnetic resonance spectroscopy (MRS) were higher in type 1 diabetic patients with hypoglycaemia unawareness than in healthy subjects during hyperglycaemia [6]. In contrast, no global alteration of brain glucose transport in type 1 diabetic subjects was found when positron emission tomography was employed for direct quantification of brain glucose uptake [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…In line with this concept cerebral glucose concentrations measured by magnetic resonance spectroscopy (MRS) were higher in type 1 diabetic patients with hypoglycaemia unawareness than in healthy subjects during hyperglycaemia [6]. In contrast, no global alteration of brain glucose transport in type 1 diabetic subjects was found when positron emission tomography was employed for direct quantification of brain glucose uptake [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…21 Despite the wide range of hypoglycemia-related signals, people with diabetes often experience poor awareness of their own symptoms, with accuracy of detection typically waning over time due to the effects of advancing age or complications of the condition, such as autonomic neuropathy. 22 Although numerous techniques (e.g., glucose sensors, skin conductors, heart-rate monitors) have been developed to facilitate early detection of hypoglycemia, 23,24 none of these, as yet, are considered reliable, practical, or suitable for use outside clinical settings.…”
mentioning
confidence: 99%
“…However, a recent article showed that blood-to-brain glucose transport, cerebral glucose metabolism, and blood flow are not increased after hypoglycemia [5]. Therefore, the pathophysiology of hypoglycemia unawareness still remains incompletely understood [10]. …”
Section: Introductionmentioning
confidence: 99%